Perubahan Efisiensi Teknis Usaha Tani Jagung pada Agroekosistem Lahan Kering - Rangga Ditya Yofa; Yusman Syaukat; nFN Sumaryanto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
EnglishThe level of corn productivity during the 2008-2018 period experienced sloping growth. From various previous research results, it is known that the use of corn production inputs is not optimal. This study aims to analyze changes in technical efficiency of corn farming and the factors that influence it on the dry land agroecosystem. The data used is National Farmer Panel data (Patanas) in 2008 and 2017 sourced from Indonesian Center for Agricultural Socio Economics and Policy Studies (ICASEPS), Ministry of Agriculture. The analytical method used are the stochastic frontier production function with the Time-Varying Decay (TVD) model, and the random-effects tobit model. The results of the analysis show that the average level of technical efficiency of corn farming reaches 70.27 percent. There was an increase in the score of technical efficiency in 2017 compared to 2008. Factors influencing this increase were the age and level of education of family heads, the share of corn farming income, and the status of land ownership. It is recommended to the government to increase the use of dry land for food crop businesses and ensure the availability of hybrid corn seeds at an affordable price.IndonesianTingkat produktivitas jagung selama periode 2008–2018 mengalami pertumbuhan yang melandai. Dari beragam hasil penelitian sebelumnya diketahui bahwa penggunaan input produksi jagung belum optimal. Penelitian ini memiliki tujuan untuk menganalisis perubahan tingkat-efisiensi teknis usaha tani jagung dan faktor-faktor yang memengaruhi-nya pada agroekosistem lahan kering. Data yang digunakan adalah data Panel Petani Nasional (Patanas) tahun 2008 dan 2017 yang bersumber dari Pusat Sosial Ekonomi dan Kebijakan Pertanian (PSEKP), Kementan. Metode analisis yang digunakan adalah fungsi produksi Stochastic Frontier dengan model Time-Varying Decay (TVD), dan model Random-Effects Tobit. Hasil analisis menunjukkan bahwa rata-rata tingkat efisiensi teknis usaha tani jagung mencapai 70,27%. Terjadi peningkatan skor efisiensi teknis pada tahun 2017 dibandingkan tahun 2008. Faktor yang memengaruhi peningkatan ini yaitu umur dan tingkat pendidikan kepala keluarga, pangsa pendapatan usaha tani jagung, dan status kepemilikan lahan. Disarankan kepada pemerintah agar meningkatkan pemanfaatan lahan kering untuk usaha tanaman pangan dan menjamin ketersediaan benih jagung hibrida dengan harga yang terjangkau.